The Contextualisation of Siyar in the Era of Nation-States and Globalisation - Hasnan Bachtiar (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2019)
This article examines the concept of Siyar and its relation to the dynamisation of Islamic law. Siyar is a discipline in Islamic law covering issues of law of war and international relations in Islamic traditions, which means conducting Muslim states in relation with other communities. The efforts of the contextualisation of Siyar have been critical primarily when Muslims have faced challenging realities of nation-states, globalisation and post 9/11. This article arguably states that Siyar needs to be reinterpreted and revitalised due to its classical idea is not compatible with the modern ideas and practices of modern polity. Its main doctrine of bifurcation of the world (dār al-Islām and dār al-ḥarb) encourages arguments and practices of the defensive and offensive jihād amongst Islamist agencies. Accordingly, Muhammadiyah contextualised Siyar through its very idea of the Negara Pancasila sebagai Dār al-‘Ahd wa al-Shahādah emphasising Indonesia as the state of negotiation between the arenas of dār al-Islām and dār al-ḥarb.